MENYISIPKAN PESAN RAHASIA KEDALAM GAMBAR DENGAN METODE BLOWFISH DAN LEAST SIGNIFICANT BIT (LSB) - Siti - Muryanah (University of Muhammadiyah Tangerang, 2020)
Current technological developments make information needs very important. However, information that becomes confidential will become public information due to insecurity of the information in the process of exchanging information from the sender to the recipient of the information. In this regard, there are several things that must be considered during the process of sending messages, namely confidentiality, integrity, availability, authenticity, and non-repudiation. On this basis, the authors combine information security with cryptographic and steganographic methods. Cryptography is the change of the original message into a secret message, while steganography is the art of inserting messages into a media so that other people do not realize that there is a secret message in the media. The cryptographic methods that I use are the Blowfish method and the LSB steganography method. The insertion method using the LSB method is the process of inserting messages by presenting binary image files or images with binary representations of secret messages to be hidden. Thus, at every pixel a 24-bit BMP image or image file can be inserted with 3 message bits. The result is a secret message successfully inserted into the picture and reduce the suspicion of others that the picture has confidential information.